Keto-enol tautomerism in the development of new drugs - Araujo de Oliveira, Ana Paula; Wegermann, Camila Anchau; Ferreira, Ana Maria Da Costa (Frontiers in Chemical Biology, 2024)
The presence of isomers is a huge challenge in the development of new medicinal or pharmaceutical agents because the main goal is to obtain the most active compound with high purity and yield. Tautomerism is a phenomenon quite common in biomolecules that also appears in many drugs, and strategies to control the corresponding desired species and related equilibrium conditions leading to efficient chemical speciation are frequently required. There are many reports in the literature about the presence of tautomers, although some articles do not properly emphasize their occurrence or their importance for the differences verified in biological activity. Herein, a discussion about tautomers observed in both metalated and non-metalated compounds and their importance in the biological properties of promising drugs is revisited. Mainly, keto-enol equilibria among imines, hydrazones, and oxindole derivatives are showcased, based on significant examples, and strategies to improve their speciation or to better elucidate their modes of action are suggested.